ON THE USE OF COMPUTER PROGRAMS IN TEACHING HIGHER MATHEMATICS FOR STUDENTS OF TECHNICAL SPECIALTIES - Zakusylo, Anatolii Ivanovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The expediency and ways of computer support of mathematical training of students of technical specialties are substantiated. Arguments in favor of a significant increase in the share of computer technology in the teaching of higher mathematics.